Current topics in the multimodality treatment of locally advanced rectal cancer. (April 2016) - Russo, Suzanne; Steele, Scott; Fredman, Elisha; Biswas, Tithi
The multimodality approach to the treatment of locally advanced rectal cancer has evolved to include neoadjuvant radiotherapy with or without concurrent chemotherapy, total mesorectal excision and adjuvant fluoropyrimidine-based chemotherapy. Though this broad strategy has yielded improvements in local control compared with historical data, overall survival remains largely unchanged. Current investigations focus on improving patient selection through new imaging modalities, improving surgical techniques, incorporating more aggressive systemic treatment regimens and the selective use of radiation. Here, we review emerging data regarding newer staging techniques, neoadjuvant chemotherapy, optimal timing of surgery, selective use of radiation and nonoperative approaches to the management of locally advanced rectal cancers.